Improving Students’ Ability in Writing Narrative Text through Picture Series in the Twelfth Grade Students of Vocational School (Lexeme : Journal of Linguistics and Applied Linguistics, 2019)
Writing is one of productive skills, and teaching writing needs to concern many aspects. One of them is teaching aid. Appropriate teaching aid, like picture series, can help students optimize their learning process in writing. The research objective is to discover the effectiveness of picture series in improving studentsâ€™ writing ability of narrative text. The writer used an experimental method. The population of this research was the students of SMKN 2 Tangerang Selatan. The samples were taken from two classes of the twelfth graders majoring in Accounting. The writer took 31 students for the samples in experiment class and 32 students in control class. The data that the writer got from the research were using the t-test formula. The findings show that using picture series is effective in improving studentsâ€™ writing ability. The result is tobserved =  2.73   and ttable = 1.67. Because to > tt , it means there is a significant effectiveness to improve in studentsâ€™ writing ability using picture series. The findings are expected to be useful for the students to help them improve their English writing ability of narrative text. Additionally, it gives information to the teachers to know appropriate teaching aids to teach writing ability for the students.